2007
DOI: 10.1364/josab.24.002259
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of fluorescence scattering by silver nanoparticles

Abstract: We study the nature of fluorescence scattering by a radiating fluorophore placed near a metal nanoparticle with the finite-difference time-domain method. Angle-resolved light-scattering distributions are contrasted with those that result when ordinary plane waves are scattered by the nanoparticle. For certain sized nanoparticles and fluorophore dipoles oriented parallel to the metal surface, we find that the highest scattered fluorescence emission is directed back toward the fluorophore, which is very differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
64
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 27 publications
6
64
0
Order By: Relevance
“…At the end of the simulation, the various field components are checked to see if they decay to zero, thus indicating that the simulation has run for a sufficiently long time for the CW information obtained by Fourier transformations to be valid. 36,37 …”
Section: Methodsmentioning
confidence: 99%
“…At the end of the simulation, the various field components are checked to see if they decay to zero, thus indicating that the simulation has run for a sufficiently long time for the CW information obtained by Fourier transformations to be valid. 36,37 …”
Section: Methodsmentioning
confidence: 99%
“…This enhances the emission rate. 15,28,29 Therefore, it is again suggested that the distances between nanoparticles and fluorophores are as small as possible.…”
Section: Introductionmentioning
confidence: 99%
“…This fact puts in evidence the importance of studying the interaction between DSs and PNs. Many articles have been devoted to the investigation of radiative and nonradiative decay rates and to the emission enhancement of molecules beside metallic nanoparticles numerically, theoretically, or experimentally [12][13][14][15][16][17][18][19][20][21]. Also, studies have reported on the near-field effect of molecules on metallic structures [22][23][24].…”
Section: Introductionmentioning
confidence: 99%